Investigation of Oil Palm Frond Properties for Use as Biomaterials and Biofuels - Mior Ahmad Khushairi, Mohd Zahari; Ahmad Muhaimin, Roslan; Mohd Ali, Hassan; Shirai, Yoshihito (Japanese Society for Tropical Agriculture, 2014)
Elaies guineensis is an oil-producing plant commonly known as oil palm. Palm oil processing produces biomass including empty fruit bunches (EFB), mesocarp fibre (MF), palm oil mill effluent (POME), palm kernel cake (PKC), shells, oil palm trunk (OPT) and oil palm frond (OPF). In 2009, a total of 83 million tons of OPF was produced (ASM, 2010) and left in the plantation for nutrient recycling. Our previous study revealed that the oil palm frond (OPF) petiole contains a large amount of sugars (Zahari et al., 2012), suggesting that it is an excellent resource for the production of biomaterials and for bioenergy. However, for OPF utilisation two problems must be addressed, namely the disturbance of the nutrient recycling and the logistics related to the transport of OPF from the plantation to the palm oil mill. Hence the objectives of the present study were to investigate the properties of each part of OPF, including petiole, stem, rachis and leaflet not only for potential use as non-food feedstock for the production of biomaterials and for bioenergy, but also for maintaining the nutrient balance in the plantation.